Pius XII, the Holocaust, and the Cold War - Phayer, Michael (Indiana Univ. Press, 2008)
Eugenio Pacelli : 1900 to 1942 -- The genocides of Polish Catholics and Polish Jews -- Pius XII's 1942 Christmas message : genocide decried -- 1943 : Pius XII reverses course -- Papal capitalism during World War II -- The first Cold War warrior -- The origin of the Vatican ratlines -- Bishop Hudal's ratline -- Looted gold and the Vatican -- Ante Pavelić : war criminal, murderer, and defender of the faith -- The biggest ratline -- An obsession with communism